P1702THROMBOTIC MICROANGIOPATHY IN KIDNEY TRANSPLANT RECIPIENTS. (6th June 2020) - Petr, Vojtěch; Hrubá, Petra; Šafránek, Roman; Dedochova, Jarmila; Krejčí, Karel; Stepankova, Sona; Machová, Jana; Slatinska, Janka; Kollár, Marek; Honsova, Eva; Dusilova Sulkova, Sylvie; Viklicky, Ondrej
Abstract: Background and Aims: Thrombotic microangiopathy (TMA) pathogenesis in kidney transplantation is poorly understood. The aim of this study was to evaluate donor and recipients risk factors for posttransplant TMA. Method: In this retrospective multicenter national study, we identified both the case and 3M protocol kidney graft biopsies in 5258 recipients with TMA (n=57, 1.1 %) in 1994-2019. To further evaluate the effect of donor kidney on TMA development, the outcomes of the pair kidney grafts from the identical donors (n=43, 6 living donor, 1 pair kidney discarded, 6 insufficient data) as control group was analyzed. Results: TMA occurred in 57 patients at 8 th (median) post-operative day. Interestingly, neither histological nor laboratory signs of TMA were present in controls but in one case where TMA was evident in both recipients and in donor zero-hour biopsy. TMA associated with acute antibody mediated rejection was found in 11 cases (19%). Basic demographics between TMA and control group were similar, however longer cold ischemia time (p < 0, 05, Figure 1) and more frequent delayed graft function (p < 0, 05) were observed in TMA group. Patients with TMA experienced lower death-censored 5-year graft survival (56 vs. 84 %) in comparison with control group (p < 0, 05, HR 2, 904 (95% CI 1, 411; 6, 127), Figure 2). Conclusion: TMA significantly affects the long-term kidney graft survival. Longer cold ischemia time was identified as the only risk factor and thus recipients genetic background is highly suspected in its pathogenesis.